Implementasi Metode SAW Dalam Menentukan Supplier Terbaik Pada PT.Senjaya Rejekimas - Tegar Muhamad Hafiez (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
In selecting the best supplier in PT. Senjaya Rejekimas still has several obstacles, such as the assessment of each supplier is still done manually, which causes the assessment process to be less accurate and inefficient. In addition, to obtain or find out information on the results of selecting the best supplier, it takes quite a long time, because you have to re-enter the value of each supplier into Microsoft Excel and make value pranks manually. Data collection methods used are interviews, observation and literature study. The decision- making method used by the author is SAW, while the system development method used is the SDLC method with UML design tools. Implementation of the program using the PHP programming language with MySQL database. Decision support systems can be used to facilitate the school in managing data, presenting information, generating reports and reducing errors in calculating values and getting accurate supplier ranking results and the application of the SAW method can improve the quality of decision making in selecting the best supplier. Based on the results of research conducted at PT. Senjaya Rejekimas got the best supplier value according to the ranking, namely PT Mitra Bangun Serasi with a value of 4.33.